Treatment in Infections by Enterobacterales Producing Extended Spectrum Betalactamase. Systematic Review - Carli Samira Aziz Delgado; José Andrés Mendoza Gaviria (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2021)
Extended spectrum beta-lactamases producing Enterobacterales have become pandemic worldwide representing a major public health threat due to poor outcomes and high mortality associated with infections by these bacteria, consequently it is essential to conduct a systematic review to document the antibiotic combination used to fight infections, in order to categorize and sort the most widely used treatments and determine the most effective ones. The electronic search was conducted since June 2020 until August 2020. The databases used were PubMed, Virtual Health Library, ScienceDirect and the Cochrane library; the following Medical Subject Headings (MESH) were used: "Enterobacterales", "infection", "beta-lactamase", "beta-lactamase inhibitors", "therapeutics", "Enterobacteriaceae/enzymology". The electronic search resulted in 1.526 articles meeting the general criteria, 1.493 articles were excluded; only 35 articles met all the inclusion criteria. there is basically no tangible difference between treatment with beta-lactam antibiotics (either combinations or carbapenem), fluoroquinolones, tetracyclines and Fosfomycin in patients without any pre-existing antibiotic resistance. It is required developing antibiotics, with the understanding that the microorganism will respond to them and resistance will develop (an evolutionary fact). Therefore, efforts to develop antibiotics and study mechanisms of resistance should be continuous, resilient, and steady